SBIRT training: how do social work students compare to medical learners?. (26th November 2021) - P. Martin, Matthew; Woodside, Summer G.; Lee, Chong; Henry, Laura; Patkar, Ashwin
ABSTRACT: Background : SBIRT (Screening, Brief Intervention, and Referral to Treatment) is an effective early intervention approach for individuals with substance misuse. The purpose of this study was to determine if medical learners are more adept at learning a brief substance use intervention compared to non-medical learners (e.g., social work students). The dissemination of SBIRT training among many helping professions can increase service delivery for substance use problems. Methods : A total of 2, 488 participants completed SBIRT training, representing 15 different disciplines and over 20 different institutions. General linear models and paired t -tests were used to investigate the effects of SBIRT training on changes in knowledge and attitude of alcohol and drug use and satisfaction. Results : There were no statistical differences in the change of satisfaction, knowledge, and attitude between medical and non-medical discipline participants. Both medical and non-medical participants had greater improvement in attitude and knowledge scores post-training. Similar improvements in attitude, knowledge, and satisfaction were observed in all the health-care discipline participants. Discussion : SBIRT skills may be transferable to disciplines including non-prescribing professionals (e.g., social work, nursing, physical therapy, rehabilitation science, and pharmacy). In an effort to expand treatment, health-care training institutions adopt SBIRT as a core competency for professional practice.